2012
DOI: 10.1158/0008-5472.can-11-3160
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Tumor-Associated Dendritic Cells In Vivo Using miRNA Mimetics Triggers Protective Immunity against Ovarian Cancer

Abstract: Modulating the activity of microRNAs (miRNAs) provides opportunities for novel cancer interventions. However, low bioavailability and poor cellular uptake are major challenges for delivering miRNA mimetics specifically to tumor cells. Here, we took advantage of the spontaneous enhanced endocytic activity of ovarian cancer-associated dendritic cells (DCs) to selectively supplement the immunomostimulatory miRNA miR-155. In vivo processing of nanoparticles carrying oligonucleotide duplexes mimicking the bulged st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
150
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 36 publications
(63 reference statements)
6
150
0
1
Order By: Relevance
“…Moreover, ectopic miR-155 expression can repolarize protumoral M2 TAMs toward an antitumoral M1 phenotype, 37 and augmenting miR-155 levels in tumor-associated dendritic cells by miRNA mimetics enhanced antitumor responses in established ovarian cancers. 38 These observations are fully in line with our data, which show impairment of classic macrophage activation upon miR-155/KD. We do not exclude, however, that miR-155 insufficiency in other hematopoietic compartments may have similar protumoral effects, as recently proposed for T cells by Huffaker et al 39 It has been suggested that miR-155 positively regulates granulocyte and monocyte development by acting on myeloid BM progenitors, 12 a compartment in which the SFFV-driven miR-155/ KD vector is active.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, ectopic miR-155 expression can repolarize protumoral M2 TAMs toward an antitumoral M1 phenotype, 37 and augmenting miR-155 levels in tumor-associated dendritic cells by miRNA mimetics enhanced antitumor responses in established ovarian cancers. 38 These observations are fully in line with our data, which show impairment of classic macrophage activation upon miR-155/KD. We do not exclude, however, that miR-155 insufficiency in other hematopoietic compartments may have similar protumoral effects, as recently proposed for T cells by Huffaker et al 39 It has been suggested that miR-155 positively regulates granulocyte and monocyte development by acting on myeloid BM progenitors, 12 a compartment in which the SFFV-driven miR-155/ KD vector is active.…”
Section: Discussionsupporting
confidence: 90%
“…priming of anti-tumor T cell responses in mice (43). These studies all concur on the general premise that miR-155 levels help control the functional phenotype of DC.…”
Section: Discussionsupporting
confidence: 63%
“…Over the years, several downstream targets of miR-155 have been identified, including suppressor of cytokine signaling 1 (21,42), SHIP1 (34)(35)(36)(46)(47)(48)(49), DC-SIGN (28), CD200 (43), and CD155 (42). Studies investigating the function of SHIP1 in ex vivo-generated and matured DCs have shown that SHIP1 plays a controversial role in DC function.…”
Section: Discussionmentioning
confidence: 99%
“…Building on the insight of these studies, and by taking advantage of the enhanced endocytic pathways of tumor-associated DCs [62], we have more recently combined the synergy between the intrinsic TLR agonistic activity of double-stranded RNA and CD40 activation with the immunostimulatory activity of miR-155. Thus, we demonstrated that Dicer substrates mimicking the sequence and structure of endogenous miR-155 are selectively taken-up by tumor-associated CD11c + MHC-II + DCs in mice growing aggressive orthotopic ovarian tumors when combined with biocompatible polymers, which synergizes with CD40 agonists [80]. Two important observations can be drawn from these studies; one, that DCs are major orchestrators of the immunosuppressive microenvironment, and two, in situ delivery of a potent antigenic stimulus is sufficient to reverse the tolerogenic phenotype, which provides a rationale for subsequent clinical testing.…”
Section: Back To Normal: In Vivo Re-programming Of Tumor Dcsmentioning
confidence: 92%